European Union development assistance for Tajikistan - Iczetkin, Aleksandra; Gajda, Olga (Destined to Cooperate? Various Dimensions of European Union Policy Towards Asian Countries, 2024)
Disparities between developed, developing, and Global South countries continue to deepen. Hence, developmental assistance for post-Soviet countries remains crucial. This chapter aims to present developmental aid for Tajikistan from the European Union. It addresses questions regarding the nature of this support. The main areas of assistance will be presented, along with the financial investments made in them. An assessment of the effectiveness of developmental policy will also be conducted, and EU assistance will be compared with aid offered by other stakeholders interested in the Central Asian region.